Tourism, Jobs, Capital Accumulation and the Economy: A Dynamic Analysis - Pasquale M. Sgro; Chi-Chur Chao; Bharat R. Hazari; Jean-Pierre Laffargue; Eden S. H. Yu (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper examines the effects of tourism in a dynamic model of trade on unemployment, capital accumulation and resident welfare. A tourism boom improves the terms of trade, increases labor employment, but lowers capital accumulation. The reduction in the capital stock depends on the degree of factor intensity. When the traded sector is weakly capital intensive, the expansion of tourism improves welfare. However, when the traded sector is strongly capital intensive, the fall in capital can be a dominant factor in lowering national welfare. This dynamic immiserizing result of tourism on resident welfare is confirmed by simulations on German data.
Keywords: O10; F11; 330; Tourism; Employment; Capital accumulation; Welfare; Tourismus; Dynamisches Modell; Außenwirtschaft; Arbeitslosigkeit; Investition; Wohlfahrtsanalyse; Theorie; Deutschland